The septin-associated kinase Gin4 recruits Gps1 to the site of cell division - Meitinger, Franz; Pereira, Gislene (Molecular biology of the cell, 2017)
Cell cycle-dependent morphogenesis of unicellular organisms depends on the spatiotemporal control of cell polarity. Rho GTPases are the major players that guide cells through structural reorganizations such as cytokinesis (Rho1 dependent) and polarity establishment (Cdc42 dependent). In budding yeast, the protein Gps1 plays a pivotal role in both processes. Gps1 resides at the bud neck to maintain Rho1 localization and restrict Cdc42 activity during cytokinesis. Here we analyze how Gps1 is recruited to the bud neck during the cell cycle. We show that different regions of Gps1 and the septin-associated kinase Gin4 are involved in maintaining Gps1 at the bud neck from late G1 phase until midanaphase. From midanaphase, the targeting function of Gin4 is taken over by the bud neck-associated protein Nba1. Our data show that Gps1 is targeted to the cell division site in a biphasic manner, via Gin4 and Nba1, to control the spatiotemporal activation of Rho1 and inhibition of Cdc42.
Gesehen am 25.09.2018